AI in health tourism: developing a measurement scale. Issue 9 (2nd September 2022) - Wang, Kangping; Kong, Haiyan; Bu, Naipeng; Xiao, Honggen; Qiu, Xuejie; Li, Jinghan
ABSTRACT: The COVID-19 pandemic created a strong urgency for the application of artificial intelligence (AI) in the tourism and hospitality industry. This paper was set to develop a scale of AI needs in health tourism. A total of 556 valid data were collected, and both exploratory and confirmatory factor analyses were employed to analyze the data. Six constructs containing 18 items were identified, and the reliability and validity were examined to reach satisfactory levels. The measurement scale developed may serve as a foundation for future research, and shed light on tourism managers, marketers, AI designers and policymakers.